2021
DOI: 10.21924/cst.6.2.2021.547
|View full text |Cite
|
Sign up to set email alerts
|

Mg/Al-CH, Ni/Al-CH and Zn/Al-CH, as adsorbents for Congo Red removal in aqueous solution

Abstract: In this study, chitosan was extracted from shrimp shells by demineralization and deproteination processes. The extracted chitosan was used to modify the layered double hydroxide and used as an adsorbent for the removal of congo red from aqueous solutions. Composites were successfully synthesized using M2+/Al (M2+ = Zn, Mg, Ni) and chitosan (CH) and the samples obtained were characterized using XRD and FTIR. The X-ray diffraction (XRD) pattern appeared at the layered double hydroxide peak of 2? = 11.63°; 23.00°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Table 2 explained the analysis of isotherm adsorption parameters, the highest adsorption capacity of RhB and MB were reached by NH-bentonite with the value 192.308 mg/g and 270.270 mg/g, respectively. The adsorption process has adhered to the Langmuir isotherm equation, confirmed by the R 2 value being closer to 1 (Chopra et al, 2012;Siregar et al, 2021). The Langmuir model described that the adsorption process was triggered by specific interaction between active site adsorbent to adsorbate and occurs in monolayer adsorption (Jović-Jovičić et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
“…Table 2 explained the analysis of isotherm adsorption parameters, the highest adsorption capacity of RhB and MB were reached by NH-bentonite with the value 192.308 mg/g and 270.270 mg/g, respectively. The adsorption process has adhered to the Langmuir isotherm equation, confirmed by the R 2 value being closer to 1 (Chopra et al, 2012;Siregar et al, 2021). The Langmuir model described that the adsorption process was triggered by specific interaction between active site adsorbent to adsorbate and occurs in monolayer adsorption (Jović-Jovičić et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, it is necessary to treat wastewater containing dyes before removing them into the waters to be safe for environmental ecosystems. Various treatment methods such as adsorption (Muslim et al, 2021;Wijaya et al, 2021;Siregar et al, 2021), biodegradation (Takkar et al, 2022;Maurya et al, 2022;Singh et al, 2022), coagulation (Mcyotto et al, 2021;El Gaayda et al, 2022), photodegradation (Dhir, 2021;Kader et al, 2022) and photocatalytic (Khan et al, 2018;Sun et al, 2022). Among some of these methods, the adsorption method is a method that is widely used for the removal of dyes because the process is cheap, simple, e ective, and environmentally friendly (Muslim et al, 2021) .…”
Section: Introductionmentioning
confidence: 99%
“…Among some of these methods, the adsorption method is a method that is widely used for the removal of dyes because the process is cheap, simple, e ective, and environmentally friendly (Muslim et al, 2021) . Several adsorbents have been studied and used for the removal of dyes, such as bio-adsorbents (Goyal et al, 2021;Akköz et al, 2019;Panchu et al, 2022), zeolites (Youssef et al, 2021Domenzain-Gonzalez et al, 2021;Abdelrahman, 2018), bentonite (Shirazi et al, 2020;Saja et al, 2020;Fabryanty et al, 2017), metal-organic frameworks (MOFs) (Sriram et al, 2021;Feng et al, 2022;Kiwaan et al, 2021), graphite (Yin et al, 2021;Verma et al, 2020;Tian et al, 2021), and layered double hydroxide (Rashed et al, 2022;Wijaya et al, 2021;Siregar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Layered double hydroxide NiAl, ZnAl, and MgAl composited with carbon-based materials such as chitosan were e ectively to remove congo red, and the ability of the composite to be used repeatedly was stable until the seventh cycle in the regeneration process (Siregar et al, 2021) . Based on the literature, it can be concluded that carbon-based supporting materials to form composites, such as hydrochar and humic acid, are suitable for use in layered double hydroxide.…”
Section: Introductionmentioning
confidence: 99%